Legalizing Cannabis as Medicine in Indonesia: Challenges and Regulations - Budiman, Arif; Budiono, Arief (Journal of Judicial Review, 2025)
Although marijuana is banned from use in healthcare in Indonesia, medical developments show its potential benefits. This research will examine Islamic views on the legalization of medical cannabis in the context of Indonesian positive law. This research will examine the regulation, legality, and implications of the use of medical cannabis in Indonesia, focusing on legal, religious, and health aspects. Given the gap between medical needs and existing regulations, this research aims to fill the knowledge gap regarding the regulation of medical cannabis in Indonesia. This research shows that regulations related to medical cannabis are contained in Law No. 35 of 2009. From a positive legal perspective, cannabis is recognized as having health benefits that are proven to help various diseases, as recorded in history. However, in the view of Islamic law, marijuana is considered haram, including for use as medicine, except in emergency conditions or for the sake of benefit. Some scholars allow the use of haram objects for treatment if there is no halal alternative available; however, if there is a halal option, it should be used. Therefore, further research on medical marijuana is needed to ascertain its benefits and conditions of use.